Proceedings of the Ocean Drilling Program 1991
DOI: 10.2973/odp.proc.sr.121.163.1991
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Petrologic Data for Basalts from Sites 756, 757, and 758: Implications for the Origin and Evolution of the Ninetyeast Ridge

Abstract: Basement lavas from Sites 756, 757, and 758 on Ninetyeast Ridge are tholeiitic basalts. Lavas from Sites 756 and 757 appear to be subaerial eruptives, but the lowermost flows from Hole 758A are pillow lavas. In contrast to the compositional variation during the waning stages of Hawaiian volcanism, no alkalic lavas have been recovered from Ninetyeast Ridge and highly evolved lavas were recovered from only one of seven drill sites (DSDP Site 214). All lavas from Site 758 have relatively high MgO contents (8-10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 46 publications
(90 reference statements)
1
22
0
Order By: Relevance
“…In contrast, all other elements presented here appear to be free from a significant crushing blank, and the shipboard powders should be adequate for future studies involving these elements. We note here in agreement with Joron et al (1990) and in contrast with Frey et al (1991) that we found no evidence for the introduction of Zn caused by crushing in the tungsten mill.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, all other elements presented here appear to be free from a significant crushing blank, and the shipboard powders should be adequate for future studies involving these elements. We note here in agreement with Joron et al (1990) and in contrast with Frey et al (1991) that we found no evidence for the introduction of Zn caused by crushing in the tungsten mill.…”
Section: Resultssupporting
confidence: 92%
“…We acknowledge that differences may be present between the absolute abundances of elements introduced into the basalts and our test silica as a result of the different abrasive properties of the two materials. Other studies have sought to eliminate this by comparing splits of the same samples prepared in agate and tungsten carbide (e.g., Frey et al, 1991). In a similar manner, we have compared the data from two samples powdered on the ship with additional samples taken from exactly adjacent pieces of the core.…”
Section: Methodsmentioning
confidence: 99%
“…The compositional signature of the basalts of the area requires the existence of a heterogeneous ASP component that mixes with the upper mantle in variable proportions [ Doucet et al , 2004; Nicolaysen et al , 2007]. Evidence of the ASP component at the southern end of the Ninetyeast Ridge on 38 Myr old volcanism, [ Frey et al , 1991; Weis and Frey , 1991] suggests that this source is long‐lived. The ASP hot spot anomaly is however supposed to be small.…”
Section: The Amsterdam‐saint Paul/southeast Indian Ridge Interaction mentioning
confidence: 99%
“…In the bottom panel C, the time axis is not linear. The Cretaceous lavas drilled from the Kerguelen Plateau and Ninetyeast Ridge are tholeiitic basalts with relatively high Zr/Nb, with the exception of ODP Site 748 where they are alkalic [ Storey et al , 1992; Frey et al , 1991]. The Oligocene flood basalts from the Kerguelen Archipelago have transitional major element compositions with intermediate Zr/Nb ratios [ Yang et al , 1998] whereas the alkalic Miocene flood basalts from the Kerguelen Archipelago have lower Zr/Nb [ Frey et al , 2000b].…”
Section: Resultsmentioning
confidence: 99%